2000
DOI: 10.1097/00000539-200012000-00036
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Toxicity of Ropivacaine and Bupivacaine at Equipotent Doses in Rats

Abstract: We compared the toxicity of systemic local anesthetics bupivacaine and ropivacaine administered at equivalent and equipotent doses. In the first experiments, 18 male Wistar rats were anesthetized with thiopental and maintained under positive controlled ventilation. Electrocardiogram, electroencephalogram, and invasive arterial blood pressure were continuously recorded. The animals were randomly assigned to receive 3 mg x kg(-1) x min(-1) bupivacaine, 3 mg x kg(-1) x min(-1) ropivacaine IV (equivalent group), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(66 citation statements)
references
References 10 publications
1
58
0
7
Order By: Relevance
“…Kundra et al, conducted a study in 60 patients for pain relief after lumbar laminectomies comparing pre-emptive caudal morphine with postoperative caudal morphine and found that VAS at eight hour, time for first postoperative analgesia and postoperative morphine consumption to be much lower and significant with pre-emptive caudal epidural morphine [15]. Ropivacaine 0.2% was the choice of local anaesthesia which provides an advantage over bupivacaine with respect to central nervous system and cardiovascular system safety index [9,18,19] and selectivity towards sensory rather than motor blockade [8].…”
Section: Discussionmentioning
confidence: 99%
“…Kundra et al, conducted a study in 60 patients for pain relief after lumbar laminectomies comparing pre-emptive caudal morphine with postoperative caudal morphine and found that VAS at eight hour, time for first postoperative analgesia and postoperative morphine consumption to be much lower and significant with pre-emptive caudal epidural morphine [15]. Ropivacaine 0.2% was the choice of local anaesthesia which provides an advantage over bupivacaine with respect to central nervous system and cardiovascular system safety index [9,18,19] and selectivity towards sensory rather than motor blockade [8].…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that icv ropivacaine produces dysrhythmias and increases artery blood pressure, which are associated with iv ropivacaine administration (Dony et al, 2000;Guinet et al, 2009).…”
Section: Discussionmentioning
confidence: 58%
“…7,9,11,12,15 Ropivacaine, which has less CV toxicity than bupivacaine, was subsequently introduced into clinical practice. 19,22 However, ropivacaine is at least 40% less potent than bupivacaine. 23 We did not compare the toxicity of dextromethorphan and dextrorphan with that of ropivacaine, although this comparison could be worthwhile investigating in the future.…”
Section: áMinmentioning
confidence: 99%